2007
DOI: 10.5944/rppc.vol.12.num.1.2007.4031
|View full text |Cite
|
Sign up to set email alerts
|

El modelo de los cinco grandes como predictor de la conducta agresiva en población infanto-juvenil

Abstract: Resumen: El presente trabajo estudia la relación entre el modelo de personalidad de los Cinco Grandes y la agresión física y verbal en un grupo de 686 sujetos (426 chicos y 260 chicas) de edades comprendidas entre 8 y 15 años. Los resultados muestran que las dimensiones de conciencia (especialmente en mujeres) y neuroticismo (especialmente en varones) son las más relevantes, aunque las dimensiones de amabilidad y extraversión también resultaron significativas principalmente en la agresión verbal. Se discute la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
(48 reference statements)
1
1
1
6
Order By: Relevance
“…It is also interesting to note the potential risk factors that were not retained in either model. Although socioeconomic level, extroversion, positive parental support, self-conflict in the application of discipline, and conflict between parents in applying discipline variables have been related to CPV and to adolescents' aggressive behaviour in other studies (e.g., Aroca-Montolío et al, 2014;Carrasco & Del Barrio, 2007;Cottrell y Monk, 2004;Gallego et al, 2019;Ibabe & Bentler, 2016;Margolin & Baucom, 2014), in the present study, we did not find a significant relationship. It is possible that these variables became non-significant after controlling for the effect of other relevant variables for CPV.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…It is also interesting to note the potential risk factors that were not retained in either model. Although socioeconomic level, extroversion, positive parental support, self-conflict in the application of discipline, and conflict between parents in applying discipline variables have been related to CPV and to adolescents' aggressive behaviour in other studies (e.g., Aroca-Montolío et al, 2014;Carrasco & Del Barrio, 2007;Cottrell y Monk, 2004;Gallego et al, 2019;Ibabe & Bentler, 2016;Margolin & Baucom, 2014), in the present study, we did not find a significant relationship. It is possible that these variables became non-significant after controlling for the effect of other relevant variables for CPV.…”
Section: Discussioncontrasting
confidence: 93%
“…Adolescents' impulsivity (e.g., Calvete et al, 2011;Ibabe et al, 2007;, traits of anger expression (Armstrong et al, 2018;Kethineni, 2004;, and substance abuse Contreras & Cano, 2015;Kethineni, 2004;Nowakowski & Mattern, 2014) have been related to increases in CPV; therefore, a positive relationship with CPV in the models studied is expected. Finally, consistently with studies that found an association of extroversion and emotional instability with aggressive behaviour in adolescents (Caprara & Pastorelli, 1993;Carrasco & Del Barrio, 2007), those variables are expected to be positively related with CPV.…”
Section: The Present Studysupporting
confidence: 75%
See 1 more Smart Citation
“…La estructura de personalidad de los 5 grandes podría predecir significativamente la conducta agresiva. Carrasco y del Barrio (2007) encontraron que las dimensiones de conciencia (especialmente en mujeres) y neuroticismo (especialmente en varones) son las más relevantes tanto para la agresión física como para la verbal, y que las dimensiones de amabilidad y extraversión también resultaron significativas para la agresión verbal. Como estos mismos autores sugieren, es conveniente considerar los diferentes tipos de agresión así como estudiar estas relaciones en chicos y chicas separadamente (Carrasco, Barker, Tremblay y Vitaro, 2006;Carrasco y del Barrio, 2007;Lynam et al, 2005;Miller, Lynam y Leukefeld, 2003).…”
Section: Introductionunclassified
“…Entre las características del niño, se ha relacionado la personalidad con este tipo de problemática (Carrasco y del Barrio, 2007). En cuanto a las prácticas de crianza, la calidad de las relaciones padres-niño está asociada con la gravedad de la desobediencia, el desafío y las pautas de conducta agresiva, y también con la persistencia de esas conductas a lo largo del desarrollo.…”
unclassified